Strategy for reducing cytotoxicity and obtaining esthetic efficacy with 15 min of in-office dental bleaching - Ortecho-Zuta, Uxua [UNESP]; de Oliveira Duque, Carla Caroline [UNESP]; de Oliveira Ribeiro, Rafael Antonio [UNESP]; Leite, Maria Luísa [UNESP]; Soares, Diana Gabriela; Hebling, Josimeri [UNESP]; Briso, André Luiz Fraga [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2022)
Objectives: Evaluate in vitro the esthetic efficacy and cytotoxicity of a bleaching gel containing 35% hydrogen peroxide (BG-35%H2O2), applied for different time intervals, on enamel coated or not with polymeric biomaterials. Materials and methods: Nanofiber scaffolds (NSc) and a primer catalyst (PrCa) were used to coat the bovine enamel/dentin discs before the application of BG-35%H2O2, according to the following groups: G1—negative control (NC, without treatment); G2, G3, and G4—BG-35%H2O2 applied for 3 × 15, 2 × 15, and 15 min; G5, G6, and G7—BG-35%H2O2 applied on enamel coated with NSc and PrCa for 3 × 15; 2 × 15, and 15 min, respectively. The culture medium with components of gel diffused through the discs was applied on MDPC-23 cells, which were evaluated regarding to viability (VB), integrity of the membrane (IM), and oxidative stress (OxS). The quantity of H2O2 diffused and esthetic efficacy (ΔE/ΔWI) of the dental tissues were also analyzed (ANOVA/Tukey; p < 0.05). Results: Only G7 was similar to G1 regarding VB (p > 0.05). The lowest value of H2O2 diffusion occurred in G4 and G7, where the cells exhibited the lowest OxS than G2 (p < 0.05). Despite G5 showing the greatest ΔE regarding other groups (p < 0.05), the esthetic efficacy observed in G7 was similar to G2 (p > 0.05). ΔWI indicated a greater bleaching effect for groups G5, G6, and G7 (p < 0.05). Conclusion: Coating the dental enamel with polymeric biomaterials reduced the time and the cytotoxicity of BG-35%H2O2. Clinical significance. Coating the dental enamel with polymeric biomaterials allows safer and faster BG-35%H2O2 application.
Keywords: Cytotoxicity; Dental bleaching; Odontoblasts; Polymeric biomaterials